1993
DOI: 10.1139/z93-087
|View full text |Cite
|
Sign up to set email alerts
|

Movements and biological statistics of lake sturgeon (Acipenser fulvescens) populations from the St. Lawrence and Ottawa River system, Quebec

Abstract: Our objective was to compare movements and biological statistics of lake sturgeon (Acipenser fulvescens) populations from two fluvial lakes on the St. Lawrence River, Lac Saint-Louis and Lac Saint-Pierre, which are main commercial fishing sectors, and from Lac des Deux Montagnes on the Ottawa River. Sturgeon can move freely among these three lakes. Lac des Deux Montagnes sturgeon differ from the other groups by their higher degree of sedentariness, slower growth, and lower condition factor. Lac Saint-Louis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 7 publications
3
61
2
2
Order By: Relevance
“…Inherited traits such as morphology, life history and/or behaviour also can be used to support designatable units under this criterion. Unfortunately, appropriate studies across the geographic range of lake sturgeon are also lacking; however, Fortin et al (1993) suggested that populations probably differ by watershed and that there also may be differentiation of sympatric populations in larger watersheds, a suggestion consistent with the results of the genetic studies cited above.…”
Section: Criterion 2) Units Identified As Genetically Distinctmentioning
confidence: 65%
See 3 more Smart Citations
“…Inherited traits such as morphology, life history and/or behaviour also can be used to support designatable units under this criterion. Unfortunately, appropriate studies across the geographic range of lake sturgeon are also lacking; however, Fortin et al (1993) suggested that populations probably differ by watershed and that there also may be differentiation of sympatric populations in larger watersheds, a suggestion consistent with the results of the genetic studies cited above.…”
Section: Criterion 2) Units Identified As Genetically Distinctmentioning
confidence: 65%
“…This may be explained by the greater longevity of females (Probst and Cooper 1954;Dumont et al 1987). Fortin et al (1993) found that by the age of maturation (20-29 years) in southern Quebec, the female:male ratio was in the order of 2:1 and by age 40, it was 6:1. Mosindy and Rusak (1991) found a similar increase in Lake of the Woods.…”
Section: Reproduction and Growthmentioning
confidence: 98%
See 2 more Smart Citations
“…Homing or site fidelity by Lake Sturgeon has previously been described (Threader and Brousseau 1986;Fortin et al 1993;Rusak and Mosindy 1997;Auer 1999;Caswell et al 2004). This area of the river is characterized by a sandy, clay substrate, which should be productive for benthic invertebrates, the primary source of prey for sturgeon.…”
Section: Discussionmentioning
confidence: 99%